Youth Engagement in Climate-Smart Agriculture in Africa: Opportunities and Challenges - Mungai, Catherine; Muchaba, Tabitha; Szilagyi, Lili; Radeny, Maren A.O.; Atakos, Vivian; Ntiokam, Divine (2018)
Engaging youth in agriculture is increasingly being recognized as a critical component of the sustainable development pathway. Worldwide, there is growing concern that young people have become disenchanted with agriculture. About 85% of the young people live in developing countries, where agriculture is likely to provide the main source of income. It is, therefore, vital that young people are actively engaged in agriculture. In order to understand the challenges and opportunities for young people in agriculture, especially in the context of a changing climate, CCAFS East Africa, CSAYN, ACLYP, ICCO Cooperation, AgriProfocus and the CGIAR Research Program on Livestock hosted a series of events and discussions in 2016 and 2017. These included three online discussion forums focusing on different themes including youth, climate-smart agriculture, agribusiness, information communication technology (ICT) and the Sustainable Development Goals (SDGs), which were hosted on the Climate and Agriculture Network for Africa (CANA) platform. Building on the online discussions, a webinar was also organized in 2017. In 2016, the youth engagement efforts culminated in a side event at the United Nations Framework Convention on Climate Change twenty-second session of the Conference of the Parties (COP22) in November, in Marrakech in Morocco. This report summarizes the outcomes of the online discussions, webinar and side event, focusing on the challenges and opportunities of youth engagement in climate-smart agriculture.